Burkina Faso Early Childhood Development : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2015)
Systems approach for better education results (SABER) early childhood development (ECD) collects, analyzes, and disseminates comprehensive information on ECD policies around the world. In each participating country, extensive multi-literature is collated and interviews are conducted with a range of ECD stakeholder including government officials, service providers, civil society, development partners, and scholars. The SABER ECD framework presents a holistic and integrated assessment of how the overall policy environment in a country affects young children’s development. This assessment can be used to identify how countries address the same policy challenges related to ECD, with the ultimate goal of designing effective policies for young children and their families. SABER ECD identifies three core policy goals that countries should address to ensure optimal ECD outcomes: (i) establishing an enabling environment; (ii) implementing widely; and (iii) monitoring and assuring quality.